Accuracy of Biometry for Intraocular Lens Implantation Using the New Partial Coherence Interferometer, AL-scan - Moon, Sang Woo (Korean J Ophthalmol, 2014)
PURPOSE: To compare the refractive results of cataract surgery measured by applanation ultrasound and the new partial coherence interferometer, AL-scan. METHODS: Medical records of 76 patients and 104 eyes who underwent cataract surgery from January 2013 to June 2013 were retrospectively reviewed. Biometries were measured using ultrasound and AL-scan and intraocular lens power was calculated using the SRK-T formula. Automatic refraction examination was done 1 month after the operation, and differences between the ultrasound group and AL-scan group were compared and analyzed by mean absolute error. RESULTS: Mean axial length measured preoperatively by the ultrasound method was 23.53 ± 1.17 mm while the lengths measured using the AL-scan were 0.03 mm longer than that of the ultrasound group (23.56 ± 1.15 mm). However, there was not a significant difference in this finding (p = 0.638). Mean absolute error was 0.34 ± 0.27 diopters in the ultrasound group and 0.36 ± 0.31 diopters in AL-scan group, which showed no significant difference (p = 0.946) in precision of predicting postoperative refraction. CONCLUSIONS: Although the difference was not statistically significant, intraocular lens calculations done by the AL-scan were nearly similar in predicting postoperative refraction compared to those of applanation ultrasound, however more precise measurements may be obtained if the axial length is longer than 24.4 mm. Except in the case of opacity in the media, which makes obtaining measurements with the AL-scan difficult, AL-scan could be a useful biometry in cataract surgery.